Daily environmental conditions determine the competition–facilitation balance for plant water status. (30th March 2015) - Wright, Alexandra; Schnitzer, Stefan A.; Reich, Peter B.; Jones, Robert
Summary Plants compete with their neighbours for a finite set of limiting resources, and this decreases individual plant performance, growth and survival. However, neighbouring plants also affect each other in positive ways. Positive facilitative effects can occur when neighbouring plants ameliorate harsh abiotic conditions (temperature, wind and high irradiation). Thus, when environmental conditions are severe, the importance of facilitation may increase. The co‐occurrence and masking effects of competition and facilitation among neighbouring plants have made it difficult to tease them apart in the past. We planted bur oak acorns (Quercus macrocarpa) into an experimental diversity gradient in a central MN grassland that provided a gradient in plant biomass. We predicted that greater biomass of neighbours would increase both competition and facilitation as measured by impacts on the minimum leaf water potential reached on any given day. Under moderate conditions, competition should predominate, but under hot/dry conditions, facilitation should become more important. We measured temperature, humidity and soil moisture in these plots for two growing seasons, as well as oak seedling leaf water potential across a range of daily conditions. On cool/humid days, plant interactions were dominated by competition for soil water: leaf water potentials of juvenile oaks were lower in plots with greater herbaceous biomass (and higher diversity). Conversely, on hot/dry days, facilitation of the microclimate determined the net effect of plants on their neighbours: leaf water potentials of juvenile oaks were higher in plots with higher herbaceous diversity and biomass. Synthesis. In terms of plant water status, plant interactions among neighbours can flip from net negative (competition) to net positive (facilitation) depending on daily abiotic conditions. The relative importance of both positive and negative interactions for plant water status may affect the overall performance of plants over time.